The Influence of Knowledge, Religiosity, Reputation, Business Actors' Income, Gender, and Trust on the Obligation to Pay Zakat in Jember - Aini, Syarifah (Journal of Islamic Contemporary Accounting and Business, 2024)
The objective of this study is to analyze the effect of each dependent variable on the independent ones and the overall influence of knowledge, religiosity, reputation, income, gender, and trust on the obligation to pay zakat. The method used in this research is quantitative, employing an explanatory research approach. The sampling technique applied is non-probability sampling, with a sample size of 140 respondents from three sub-districts in Jember Regency: Sumbersari, Kaliwates, and Patrang. The analysis technique used is multiple regression. The results of this study indicate that, partially, knowledge, religiosity, reputation, income, and trust have a positive effect on the obligation to pay zakat, whereas gender has a negative effect on zakat payment.